Pharmacological approaches for lysosomal storage diseases - Kaya, E (2019)
Niemann–Pick disease Type C (NPC) is a neurodegenerative lysosomal storage disorder that arises from defects in lysosomal proteins involved in intracellular lipid trafficking. Cellular pathology leads to clinical neurological manifestations, including ataxia. The anti-vertigo drug N-Acetyl-DL-Leucine (ADLL) has been found to be beneficial for treating vestibular anomalies and cerebellar ataxia. ADLL has also been found to ameliorate cerebellar symptoms in 12 NPC patients treated with this drug in observational clinical studies. However, the mode of action of this drug requires further study. This project has investigated the effects of ADLL and other leucine amino acid derivatives in in vitro and in vivo models of NPC. We found that ADLL, and its individual enantiomers acetyl-l-leucine (ALL) and acetyl-d-leucine (ADL) improve symptoms of ataxia in a mouse model of NPC (Npc1-/-). However, when ADLL and ALL were administered pre-symptomatically to Npc1-/- mice they were neuroprotective and ADLL synergised with the standard of care drug, miglustat. Altered energy metabolism was implicated as the mechanism of action in Npc1-/- mice. A neuroprotective effect of ADLL was also demonstrated in a mouse model of GM2 gangliosidosis (Sandhoff disease mouse) with differential effect on metabolism. We also explored the efficacy of natural, non-acetylated forms of leucine including DL-leucine, L-leucine, D-leucine and an ethyl ester form of l-leucine and found that N-acetylation of either L-leucine or D-leucine led to increased efficacy in vivo in Npc1-/- mice. Interestingly, esterification provided neuroprotective effect to L-leucine, which was not seen with N-acetylation. NPC1 null CHO cells responded to all leucine isomers in terms of correction of mitochondrial volume and mitochondrial reactive oxygen species defects characteristic of NPC but also reduced lysosomal volume and lipid storage. Finally, we performed discovery proteomics to identify ALL interacting proteins in NPC1 cells and found 9 potential interactors that could represent new therapeutic targets.